NZMSA President report - Indira Fernando (New Zealand Medical Student Journal)
Kia ora! Ko Indira Fernando toku ingoa. I am the outgoing %&%4 NewZealand Medical Students’ Association (NZMSA) President, and it has been my privilege to serve the NSMSA for the past four years. The NZMSA is the national medical student representative body in Aotearoa, advocating on behalf of all medical students across the country. In 2024, we’ve been busy creating amazing events, pushing for important system changes, and working with our partner organisations to enhance the experience of our members while at medical school and beyond.